On Atheist Spirituality. Issue 2 (November 2015) - Crocker, Geoff
Abstract : The author of this article has created an inclusive website devoted to 'an exploration of the meaning of spirituality for atheists'. The article draws on his studies in this field as well as his own developing ideas. Its purpose is to open up these ideas for wider debate.